Joint Pains in Perimenopause/ Menopause - Annil Mahajan; Sudhaa Sharma; Vishal R Tandon (Dr. Annil Mahajan, 2023)
Life expectancy has increased over the time period and thus the proportion of elderly population is rapidly increasing in the developed as well as the developing world. Females live a longer life & are thus more prone to the onslaught of various chronic diseases including musculo-skeletal diseases. The prevalence of musculoskeletal diseases is highest amongst the elderly and frequently causes disability, impairments, handicaps, job loss, dependency and great socioeconomic burden. It is reported that the most common menopausal symptoms are somatic (65.9%), psychological (46.0%) & urogenital symptoms (30.5%), whereas musculoskeletal pain is reported in more than 50% of the women. Thus, it is very important to address musculoskeletal issues of forty plus women.